Cross-spellbound - Abu Bakar, Siti Zarikh Sofiah; Zin Khami, Nabil Syakir; Roslan, Roshiqal; Sulaiman, Sahil; Mohd Johari, Mohd Akmal Faiz (2020)
Spelling is the sacred pillar of all words. Misspelled words are calamitous. Cross-Spellbound is a gold mine to enhance ESL students' skill in identifying and practicing the correct spelling for common misspelled English words. In a form of crossword puzzles, the students will be able to enjoy the extraordinarily amusing experience in trying to get the correct spelling for all words based on the clues provided. Adding to the fun, the students will be challenged by three difficulty levels namely warrior (easy), elite(intermediate), and master(hard). They should also complete each level within the stipulated time. Acing each level will definitely boost their confidence in using the English words, especially in academic writing purposes. Other than that, as students all around the globe are also challenged by the unwelcomed arrival of Covid-19 pandemic, this educational game should be beneficial in reducing their stress while gaining precious English spelling knowledge. Besides, since Open and Distance Learning (ODL) requires a more independent and student-centered learning process, Cross-Spellbound is one of the best wagons to jump on. Cross-Spellbound further serves its novelty by providing complete instructions to guide the potential players. While online games are taking the limelight in most educational areas, printed materials should not be left out as the experience from the sense of touch activities as scratching the words on paper could be one of the best spells to charm an individual.